Clinical characteristics and outcomes of toxoplasmosis among transplant recipients at two US academic medical centers. Issue 4 (1st June 2021) - Adekunle, Ruth O.; Sherman, Amy; Spicer, Jennifer O.; Messina, Julia A.; Steinbrink, Julie M.; Sexton, Mary Elizabeth; Lyon, George Marshall; Mehta, Aneesh K.; Phadke, Varun K.; Woodworth, Michael H.
Abstract: Toxoplasma gondii can cause severe opportunistic infection in immunocompromised individuals, but diagnosis is often delayed. We conducted a retrospective review of solid organ transplant (SOT) and hematopoietic stem cell transplant (HSCT) recipients with toxoplasmosis between 2002 and 2018 at two large US academic transplant centers. Patients were identified by ICD‐9 or ICD‐10 toxoplasmosis codes, positive Toxoplasma polymerase chain reaction test result, or pathologic diagnosis. Data were collected regarding transplant type, time from transplant to toxoplasmosis diagnosis, clinical and radiographic features, and mortality at 30 and 90 days. Twenty patients were identified: 10 HSCT recipients (80% allogeneic HSCT) and 10 SOT recipients (60% deceased donor renal transplants). Rejection among SOT recipients (70%) and graft‐versus‐host disease (GVHD) prophylaxis among HSCT recipients (50%) were frequent. Median time from transplant to toxoplasmosis diagnosis was longer for SOT than HSCT (1385 vs. 5 days, P ‐value .002). Clinical manifestations most commonly were encephalitis (65%), respiratory failure (40%), renal failure (40%), and distributive shock (40%). Cohort 30‐day mortality was 45%, and 90‐day mortality was 55%. Diagnosis was postmortem in 25% of the cohort. Further evaluation of toxoplasmosis screening is needed for noncardiac SOT recipients, HSCT recipients with GVHD, and periods of increased net immunosuppression.